A self-reported cross-sectional study on the oral function and the quality of life in children with stunted growth - Sianturi, Eunike; Primarti, Risti Saptarini; Setiawan, Arlette Suzy (Frontiers in Pediatrics, 2023)
Background: Failure to catch up with growth in toddlerhood will stunt elementary school children, which continues in cognitive decline and oral motor coordination. Verbally motor skills play an essential role in the oral function of the stomatognathic system, which includes mastication, swallowing, and speech. Therefore, early attention to disorders of the oral function of the stomatognathic system can avoid complications in children's nutritional status and quality of life. Objective: to analyze the correlation of oral function of the stomatognathic system with Oral Health-Related Quality of Life in stunting children. Methods: This cross-sectional study correlates with 58 children aged 7-12 years with a history of stunting in toddlerhood in Pasir Jambu District, Bandung Regency. The oral function of the stomatognathic system was evaluated by Adapted Orofacial Myofunctional Assessment Protocol and OHRQoL with Child Oral Health Impact Profile Short Form (COHIP-SF 19). Results: The results were statistically analyzed using Spearman's Rank Correlation and Kendall Coefficient of Concordance correlation tests. The results showed that the research subjects had a significant relationship in each variable and the three variables of the oral function of the stomatognathic system (chewing, swallowing, and speech) with OHRQoL with a p-value <0.05. The study concluded that the oral function of the stomatognathic system (chewing, swallowing, and speech) is related to OHRQoL in stunted growth children